A low level of reactive oxygen species selects for primitive hematopoietic stem cells that may reside in the low-oxygenic niche - Jang, Yoon-Young (American Society of Hematology, 2007)
A low-oxygenic niche in bone marrow limits reactive oxygen species (ROS) production, thus providing long-term protection for hematopoietic stem cells (HSCs) from ROS stress. Although many approaches have been used to enrich HSCs, none has been designed to isolate primitive HSCs located within the low-oxygenic niche due to difficulties of direct physical access. Here we show that an early HSC population that might reside in the niche can be functionally isolated by taking advantage of the relative intracellular ROS activity. Many attributes of primitive HSCs in the low-oxygenic osteoblastic niche, such as quiescence, and calcium receptor, N-cadherin, Notch1, and p21 are higher in the ROS(low) population. Intriguingly, the ROS(low) population has a higher self-renewal potential. In contrast, significant HSC exhaustion in the ROS(high) population was observed following serial transplantation, and expression of activated p38 mitogen-activated protein kinase (MAPK) and mammalian target of rapamycin (mTOR) was higher in this population. Importantly, treatment with an antioxidant, a p38 inhibitor, or rapamycin was able to restore HSC function in the ROS(high) population. Thus, more potent HSCs associated with the low-oxygenic niche can be isolated by selecting for the low level of ROS expression. The ROS-related signaling pathways together with specific characteristics of niche HSCs may serve as targets for beneficial therapies.